Pharmaceutical Chaperones and Proteostasis Regulators in the Therapy of Lysosomal Storage Disorders: Current Perspective and Future Promises - Mohamed, Fedah E.; Al-Gazali, Lihadh; Al-Jasmi, Fatma; Ali, Bassam R. (Frontiers in Pharmacology, 2017)
Different approaches have been utilized or proposed for the treatment of lysosomal storage disorders (LSDs) including enzyme replacement and hematopoietic stem cell transplant therapies, both aiming to compensate for the enzymatic loss of the underlying mutated lysosomal enzymes. However, these approaches have their own limitations and therefore the vast majority of LSDs are either still untreatable or their treatments are inadequate. Missense mutations affecting enzyme stability, folding and cellular trafficking are common in LSDs resulting often in low protein half-life, premature degradation, aggregation and retention of the mutant proteins in the endoplasmic reticulum. Small molecular weight compounds such as pharmaceutical chaperones and proteostasis regulators have been in recent years shown to be promising approaches for overcoming some of these protein processing defects. These compounds are thought to enhance lysosomal enzyme activity by specific binding to the mutated enzyme or by manipulating components of the proteostasis pathways promoting protein stability, folding and trafficking and thus enhancing and restoring some of the enzymatic activity of the mutated protein in lysosomes. Multiple compounds have already been approved for clinical use to treat multiple LSDs like Migalastat in the treatment of Fabry disease and others are currently under research or in clinical trials such as Ambroxol hydrochloride and Pyrimethamine. In this review, we are presenting a general overview of LSDs, their molecular and cellular bases, and focusing on recent advances on targeting and manipulation proteostasis, including the use of pharmaceutical chaperones and proteostasis regulators, as therapeutic targets for some LSDs. In addition, we present the successes, limitations and future perspectives in this field.